A comparative aerodynamic feasibility study of fluidic winglets for a conventional transport aircraft wing - Sridhar, Shivani (Cranfield University, 2026)
A significant proportion of the total aerodynamic drag encountered by a commercial aircraft during cruise is induced drag. Conventional winglets have proven to effectively reduce the induced drag; however, they introduce additional structural weight and geometric complexity. As an alternative to conventional winglets, fluidic winglets have been proposed. The fluidic winglet concept involves the fluid injection/ suction at the wingtip to reduce vortices without major structural modifications. The present work examines the aerodynamic characteristics of a fluidic winglet concept applied to a representative narrow-body transport aircraft wing. By comparing multiple wingtip configurations under consistent cruise conditions, the study seeks to clarify the aerodynamic influence of fluidic injection on lift, drag, and vortex behaviour, and to position fluidic winglets relative to established passive wingtip devices within the broader context of induced-drag reduction research. The results highlight the potential of fluidic winglets as a non-structural induced drag-reduction technique for commercial transport aircraft.
Keywords: Fluidic Winglets; Active Flow Control; Computational Fluid Dynamics (CFD); Aerodynamics; Wingtip Vortices; Induced Drag Reduction; Blended Winglets; Aircraft Performance; Boeing 737-800; Aerospace Engineering; Lift-to-Drag Ratio; Wingtip Devices; Parametric Analysis